Chronic Lymphocytic Leukemia as an Unusual Cause of Rapid Airway Compromise - Adrian R. Bersabe; Joshua T. Romain; Erin E. Ezzell; John S. Renshaw (Case Reports in Oncological Medicine)
Chronic Lymphocytic Leukemia (CLL) is the most prevalent form of non-Hodgkin’s lymphoma (NHL) in Western countries predominantly affecting adults over the age of 65. CLL is commonly indolent in nature but can present locally and aggressively at extranodal sites. Although CLL may commonly present with cervical lymphadenopathy, manifestation in nonlymphoid regions of the head and neck is not well described. CLL causing upper airway obstruction is even more uncommon. We describe a case of a patient with known history of CLL and stable lymphocytosis that developed an enlarging lymphoid base of tongue (BOT) mass resulting in rapid airway compromise.